A practical beamsteering algorithm with low phase fluctuation for WCDMA/HSUPA uplink using transmit power control bits as feedback - Schröter, Simon; Weigel, Robert; Fischer, Georg; Kölpin, Alexander (19th International Conference on Microwave Radar and Wireless Communications (MIKON), 2012, 2012)
So called open loop transmit diversity algorithms for the uplink of HSPA are a topic of recent studies within the 3rd Generation Partnership Project (3GPP). These algorithms use the power control commands of the fast power control mechanism as a feedback information to iteratively determine the antenna weights, thus making them compatible with existing networks and procedures. In this paper, a novel practical beamsteering algorithm is presented. Simulations show, that the transmit power at the UE terminal can be reduced by 3.28 dB compared to the reference case of only one transmit antenna, thus improving the UE's battery life. Moreover, the novel algorithm exhibits a significantly lower rate of change of the transmitted signal's absolute phase than the algorithms presented within the 3GPP studies, which means less irritation to the receiver at the Node B.
elib2cris::1512001600,schroeter2012

A Systematic Approach for Designing Beamsteering Algorithms for the Uplink of UMTS by Evolutionary Optimization Techniques - Schröter, Simon (IEEE Forum on Signal Processing for Radio Frequency Systems, 2013)
elib2cris::1512001600,schroeter2013

Beamsteering for the Uplink of UMTS using Transmit Power Control Bits to iteratively determine the Antenna Weights - Schröter, Simon; Weigel, Robert; Fischer, Georg (IEEE International Conference on Wireless Information Technology and Systems (ICWITS), 2012, 2012)
elib2cris::1512001600,schroeter2012a

Demonstrator of a Scanning Receiver Subsystem for Cognitive Professional Wireless Microphone Systems - Schröter, Simon; Zimmermann, Lars; Schwender, O.; Fischer, Georg; Kölpin, Alexander (Technical Symposium at ITU Telecom World 2011, 2011)
ProfessionalWireless Microphone Systems (PWMS), transmitting voice and music in live events such as concerts or conferences, demand the highest level of sound quality and reliability. Dropouts, noise and interference have to be prevented at any moment of the transmission. At present, these requirements can be fulfilled as PWMS utilize locally unused TV channels and thus operate in a protected radio environment. However, in the near future, the “Digital Dividend” will open the spectrum to other users, leading to less spectrum allocation to PWMS. In order to maintain the high quality of service of the radio links, the Specialist Task Force STF386 on Cognitive Programme Making and Special Events (C-PMSE) of the European Telecommunications Standards Institute (ETSI) proposed a proactive cognitive approach. A major part of this proposition is a Scanning Receiver Subsystem (SCS) that monitors the current spectrum occupation according to which a Cognitive Engine can dynamically configure the radio links. The SCS is composed of multiple Scanning Receivers (SCR) that measure the spectrum occupation at different locations within an event site and one or more Scanning Receiver Controllers (SCC). The SCC combine these observations to determine positions of interferers and estimate their future locations as well as their impact on the microphone links. This paper reviews the current activities of ETSI for standardization of a cognitive wireless microphone system with an in depth focus on the scanning receiver subsystem. Furthermore, the hardware of a low-cost scanning receiver, which has been developed and tested at our institute, is presented. The proposed receiver architecture fulfills the spectrum sensing capabilities recommended by ETSI and can be built at an affordable price, allowing the described proactive cognitive radio system to be realized.
elib2cris::1512001600,schroeter2011

Employing Evolutionary Optimization for Designing Practical Beamsteering Algorithms for the Uplink of UMTS with Transmit Power Control Bits as Feedback - Schröter, Simon; Weigel, Robert; Fischer, Georg (International Congress on Ultra Modern Telecommunications and Control Systems and Workshops (ICUMT), 2013)
elib2cris::1512001600,schroeter2013a

Enhancing Open Loop Beamsteering Performance for the Uplink of UMTS/HSPA+ under Discontinuous Transmission - Schröter, Simon; Rieß, Steffen; Weigel, Robert; Fischer, Georg (IEEE Radio and Wireless Symposium (RWS), 2014)
So called open loop transmit diversity algorithms for the uplink of UMTS use the power control commands as feedback to iteratively determine the antenna weights. The algorithms presented in literature so far are designed for continuous transmission. The UMTS standard, however, also allows discontinuous uplink transmission (DTX), which impairs the performance of these algorithms. This paper studies these impairments and proposes a method to design transmit diversity algorithms with improved performance in a DTX scenario. With such improved algorithms, the transmit power gain is 1.4 dB in DTX, which is an improvement of 0.7 dB over conventional non-DTX diversity algorithms.
elib2cris::1512001600,schroeter2014

Intelligente Funkmikrofone - Spektrumserfassung für Cognitive-Radio-Systeme - Rieß, Steffen; Brendel, Johannes; Schröter, Simon; Fischer, Georg (2013)
Die Hersteller von professioneller, drahtloser Produktionstechnik sehen sich zunehmend mit steigenden Anforderungen für den interferenzfreien Betrieb ihrer Systeme konfrontiert. Die Gründe dafür liegen in der Digitalen Dividende sowie Änderungen in der Regulierung durch die Bundesnetz-agentur im Frequenzbereich von 470-862 MHz. Ein Ansatz zur Lösung dieser Problematik stellt die Cognitive-Radio-Technologie dar, wobei die vorherrschende Funkumgebung überwacht und daraus ggf. die Entscheidung für einen Frequenzwechsel im Falle einer Störung getroffen wird.
elib2cris::1512001600,riess2013a

Noise Floor Dependent Data Fusion for Reliable REM Generation with a Spectrum Sensing Grid - Brendel, Johannes; Rieß, Steffen; Schröter, Simon; Fischer, Georg (IEEE Symposium on Computers and Communications, 2014)
For several years the cognitive radio (CR) technology is under research as promising solution supporting the efficient utilization of the scarce radio frequency spectrum. The cognitive cycle enables the adaptation of operating parameters according to observations made from the environment. A radio environment map (REM) which contains data from spectrum sensing devices was identified to be an adequate tool to realize CR systems. In this contribution the challenges in generating a REM from sensor nodes with limited dynamic range is pointed out. Afterwards, the noise floor dependent data fusion (NDDF) algorithm is proposed. It is able to generate a reliable REM in a fusion center of a sensing grid. The algorithm merges spectrum measurements from collocated sensor nodes to reduce the amount of data whilst preserving all advantages gained from macro diversity by taking into account the noise floor of each sensor. The algorithm has been verified with measurements in the laboratory and a measurement study at the fairground of Berlin shows the applicability of the NDDF algorithm.
elib2cris::1512001600,brendel2014

Performance Improvement of UMTS Uplink Beamsteering with Limited Feedback at Higher Terminal Velocity by Designing Adapted Algorithms - Schröter, Simon; Brendel, Johannes; Weigel, Robert; Fischer, Georg (International Conference on Communications(ICC), 2014)

Signal detection and cooperative sensing with sensor nodes with limited dynamic - Brendel, Johannes; Rieß, Steffen; Schröter, Simon; Weigel, Robert; Fischer, Georg (IEEE International Workshop on Cognitive Cellular Systems (CCS), 2014)
The paper investigates the performance of the energy detector in fading environments under the constraint, that each sensor has only a limited dynamic range. First, the effects which limit the dynamic of a sensor node are discussed before the influence on the energy detector is analyzed. Simulations are presented how cooperative spectrum sensing affects the detection probability and it is shown that a sensing network with limited dynamic can gain much more from cooperation compared to a sensor network with ideal sensor nodes.
elib2cris::1512001600,brendel2014a

The Spectrum Sensing Network: Information Acquisition for the Cognitive PMSE System - Rieß, Steffen; Brendel, Johannes; Stöckle, Andreas; Schröter, Simon; Rose, Richard; Fischer, Georg (Shaker Verlag, 2014)
Accessing the frequency spectrum in a dynamic way has been discussed since several years. The Cognitive Radio (CR) technology was identi ed as enabler in order to use the spectral resources in a more e cient way. However, to guarantee interference free operation between multiple services, spectrum sensing plays a major role of designing such a system. This contribution focuses on the realization of the Spectrum Sensing Network (SSN) that has been developed during a research project in Germany. The SSN involves multiple sensor nodes consisting of a receiver with broadband antenna which are connected to a central controller that is in charge of handling the interfaces and acquired data of the SSN. With this setup it is possible to generate an accurate radio environment map, i.e. power over frequency, time and location, in the UHF frequency range from 470 to 870 MHz. After a short introduction to the system requirements and a project overview, attention is paid to the necessary components of such a distributed sensing grid. The measurement results and the discussion of possible advantages of a SSN show the added value for a CR system. Although, the application and demonstration was based on the improvement of operating conditions for Professional Wireless Microphone Systems (PWMS), the originated eld trial platform is open for reasearch activities related to other CR systems in this frequency range.
elib2cris::1512001600,riess2014
Keywords: PMSE; cognitive radio; spectrum sensing; sensing network; sensing grid; scanning controller; scanning receiver; scanning antenna; radio environment map; data fusion